Pengaruh Kompetensi Pedagogik Guru terhadap Prestasi Belajar Siswa Kelas XI di SMK Negeri 1 Siatas Barita Tahun Pembelajaran 2023/2024 - Rini Jayanti Lumbantoruan; Rogate Artaida Tiarasi Gultom; Justice Z.Z Panggabean (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
The purpose of this study was to determine whether or not there is an effect of teacher pedagogical competence on the learning achievement of class XI students at SMK Negeri 1 Siatas Barita. The method used in this research is the quantitative research method with an infeireinsiial statistical approach. The population is the total number of students in class XI of SMK Negeri 1 Siatas Barita which amounts to 426 people and a sample of 65 is determined using random sampling technique. Data were collected with a closed questionnaire of 31 items. From the validity test obtained rxy for variable X questionnaire, namely item number 1 to item number 31, it is known that 29 items are valid because rcount (between 0.323 to 0.624) > rtable = 0.312 and 2 items are invalid because rcount (0.177 to 0.269) < rtable = 0.312 (item numbers 4 and 13). The results of data analysis show that there is a positive and significant influence of teachers' pedagogical competence on the learning achievement of class XI students at SMK Negeri 1 Siatas Barita as evidenced by the following data analysis: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.536 > rtable (α=0.05, n=65) = 0.244 thus it is known that there is a positive relationship between variable X and variable Y. b) significant relationship test obtained Thitung value = 5.045 > table (α=0.05, dk=n-2=63) = 2.000 thus there is a significant relationship between variable X and variable Y. 2) Effect test: a) Regression equation test, obtained regression equation Y ̂ = “66.265”+0.184X. b) Regression determination coefficient test (r2) = 28.8%. 3) Hypothesis testing using the F test obtained Fhitung> Ftabel, namely 25.457> 4.00. So it can be concluded that the teacher's pedagogical competence has a positive and significant effect on the learning achievement of class XI students at SMK Negeri 1 Siatas Barita.